A case of tracheobronchial amyloidosis with emphasis on differential diagnosis - Anyfanti, Foteini; Dubak, Marija; Bollow, Matthias; Ewig, Santiago (Pneumologie, 2023)
Tracheobronchial amyloidosis is a manifestation of amyloidosis of the respiratory tract characterized by focal or diffuse deposition of amyloid in the submucosa of the trachea and proximal bronchi. Tracheobronchial amyloidosis is not associated with systemic amyloidosis or pulmonary parenchymal involvement. It affects predominantly men aged over fifty. Depending on the part of the tracheobronchial tree that is affected, stenosis of the airways causes a variety of unspecific symptoms. Diagnosis is reached by means of typical presentation in CT scan followed by bronchoscopy and histopathological confirmation. Tracheobronchial amyloidosis should be borne in mind in the differential diagnosis of patients with chronic cough and/or dyspnea or recurrent respiratory infections.
Keywords: tracheobronchiale Amyloidose; Differenzialdiagnose; radiologische und bronchoskopische Befunde